PENINGKATAN AKURASI SHOOTING MELALUI VARIASI SHOOTING DINAMIS PADA ATLET SEPAKBOLA SSB GARUDA II - Fadli, Zen; Rahmad Sihombing , Ronal; Sastrawan Harahap, Agustin; Masmur Sembiring, Heri (Fakultas Ilmu Keolahragaan Unimed, 2024)
This study aims to examine the effect of dynamic shooting variation training on shooting accuracy among athletes at Sekolah Sepakbola (SSB) Garuda II Tanjung Jati Langkat. The research design used was a quasi-experimental design with pre-test and post-test. The population consisted of all 14 athletes of SSB Garuda II, and the sample was randomly selected. The research instrument was a shooting accuracy test conducted before and after the training period. The results showed a significant improvement in shooting accuracy after being given dynamic shooting variation training. Paired t-test analysis indicated a significant difference between pre-test and post-test results, with a significant t-value. Based on the study results, it is concluded that dynamic shooting variation training is effective in improving shooting accuracy in soccer athletes. This study recommends that soccer coaches adopt this training method as part of their regular training program to enhance athletes' shooting skills